2006
DOI: 10.1097/01.prs.0000210663.59939.02
|View full text |Cite
|
Sign up to set email alerts
|

Composite Anterolateral Thigh???Fascia Lata Flap: A Good Alternative to Radial Forearm???Palmaris Longus Flap for Total Lower Lip Reconstruction

Abstract: This flap is a good choice for reconstruction of the extensive head and neck defects. We think that anterolateral thigh-fascia lata composite flap has maximum reconstructive capacity and minimal donor-site morbidity. This flap has many advantages over the radial forearm flap and should replace to the composite radial forearm palmaris longus tendon flap when total lower lip reconstruction is concerned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 19 publications
1
63
0
Order By: Relevance
“…13 The vascularized fascia strip of ALT flap woven into the remaining lip muscle restores a complete ring of the oral sphincter. 21,23 Theoretically, with adequate tension, static suspension and dynamic function can be achieved in a single reconstruction with excellent symmetry of the reconstructed lip. However, 7 patients still underwent secondary procedures to improve dynamic oral incontinence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 The vascularized fascia strip of ALT flap woven into the remaining lip muscle restores a complete ring of the oral sphincter. 21,23 Theoretically, with adequate tension, static suspension and dynamic function can be achieved in a single reconstruction with excellent symmetry of the reconstructed lip. However, 7 patients still underwent secondary procedures to improve dynamic oral incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17]20,23 This technique offers many advantages such as large and pliable skin paddle, long vascular pedicle with a large diameter, and suitability for a simultaneous 2-team approach. Additionally, when compared with the radial forearm flap, the ALT flap sacrifices no major artery, and the donor-site defect can usually be closed primarily.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many patients still exhibit drooling, especially when speaking or eating. 12 In our case, a local flap could not be applied because of the lack of any residual lip tissue or oral mucosa; for such large defects, free tissue transfer is the first choice of reconstruction. There are few reports of reconstructing complete lip defects in the literature.…”
Section: Discussionmentioning
confidence: 95%
“…The reconstructive choice for lip defect was according to the defect size and area. Yildirim et al 12 reported that defects larger than 30% but smaller than 80% of the lower lip can be reconstructed with local flaps (e.g., advanced oral mucosal flaps, 5,6 extended lip flaps, 13,14 tongue flaps, or V-Y advancement flap 15 ). However, if the defect includes more than 80% of the lower lip, successful reconstruction is difficult because all of these methods allow only a static suspension of the reconstructed lip to the oral commissure.…”
Section: Discussionmentioning
confidence: 99%